Trade liberalization, market efficiency and productivity growth: A smooth transition approach on Indian firms - Nan Geng (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
This paper employs the Time Varying Panel Smooth Transition Regression (TV-PSTR) model to investigate the effects of India's dramatic trade liberalization starting from 1991 on market efficiency and productivity growth using Indian manufacturing firm data. We find that the effects of liberalization do follow a smooth transition process instead of previously assumed instantaneous "big-bang" shift just after reforms. It actually took years for the Indian firms to start to react to the reforms, and the transitional impact of reforms takes approxi- mately 4-8 years to complete, with different timing across industries. There is strong evidence of increase in competition, which pushes down the markup and make it possible to get welfare gains from reduction of dead weight losses. In response to trade reforms, most industries, which suffer most from the shrinking of market size experienced no change or falling total factor productivity (TFP) growth; whereas leather industry, as the industry which benefit most from economy of scales, enjoyed a huge TFP growth in response to reforms. This evidence is consistent with the endogenous growth model prediction, which says TFP growth after liberalization depends on whether trade is encouraging R&D and innovation or discouraging it.
Keywords: C52; D24; F12; F13; L60; 330; Panel Smooth Transition Model; Market Efficiency; Productivity